THE EFFECTIVENESS OF YOUTUBE PLATFORM LEARNING MEDIA TO IMPROVE STUDENT UNDERSTANDING IN SOCIAL STUDIES SUBJECTS - Marsiana, Erena - (Universitas Lambung Mangkurat, 2024)
The use of learning media to enhance students' understanding of subjects has been implemented by social studies teachers. However, the utilization of YouTube as an alternative medium still requires further study. This research aims to describe the effectiveness of using YouTube as a learning medium to improve students' understanding of the social studies topic on social mobility. The study employs a classroom action research (CAR) design to improve students' comprehension and learning outcomes. The CAR was conducted in three cycles, with each cycle consisting of problem analysis, a description of findings, and solutions. The research was conducted with 30 eighth-grade students at SMPN 5 Kusan Hilir. The results indicate that students' understanding of the social studies topic on social mobility improved after the application of YouTube as a learning medium. This is evidenced by the post-test results from the third cycle, where 100% of the 30 students scored above the minimum competency standard (MCS). In other words, students' understanding improved by 90% with the implementation of YouTube as a learning medium in the second and third cycles.